ID 114 – Progressive MCI proved with vMRI shows lower delta ERO than stable MCI at baseline: A longitudinal study. Issue 3 (March 2016) - Emek-Savaş, D.D.; Çavuşoğlu, B.; Güntekin, B.; Ada, E.; Başar, E.; Yener, G.G.
Abstract : Objective: Decreased delta event-related oscillations (ERO) have been reported in prior studies of Alzheimer's disease (AD) and mild cognitive impairment (MCI); however no study has examined its utility in predicting disease progression. In this study, we examined the longitudinal changes in brain dynamics of MCI by using delta ERO and volumetric MRI (vMRI). Methods: Twenty-two MCI and 23 matched control subjects were included. Peak-to-peak amplitudes of delta (0.5–3.5 Hz) auditory target ERO and vMRI were measured at baseline and a year later. The ERO and vMRI of stable and progressive MCI were compared. Results: Decreased amplitudes of delta ERO were found in MCI for baseline and follow-up [ F 1.43  = 11.394, p  = 0.002]. Progressive MCI had lower delta ERO than stable MCI at F 3 electrode site at baseline. vMRI revealed that MCI had lower volumes at baseline in whole brain and left hippocampus, and at follow-up in whole brain, right and left hippocampi. Moreover, a moderate correlation was found between left hippocampus volumes and delta ERO at C4 electrode site. Conclusions: These findings indicate that delta ERO may detect early changes in MCI and can be a useful tool to predict disease progression. Brain oscillatory responses have the potential to be used as biomarker in MCI.